Financial Ratio Analysis, in Measuring Financial Performance (Case Study on PT. Bank Central Asia Tbk.) - Try Andhini Larasati Sekar Arum; Nitri Mirosea; Yuli Lestari Labangu (Takaza Innovatix Labs Ltd., 2024)
This study aims to analyze the financial performance of PT Bank Central Asia Tbk (BCA) listed on the Indonesia Stock Exchange during the period 2022–2024 using an analysis of liquidity, solvency, and profitability ratios. Data was collected through documentation methods and analyzed descriptively using financial ratios and banking ratios approaches. The results of the study show that in general, BCA's financial condition is in a healthy state. From the liquidity aspect, the loan to deposit ratio (LDR) shows a stable increase, indicating the bank's ability to distribute funds optimally. In terms of solvency, although the debt to asset ratio (DAR) and debt to equity ratio (DER) decreased, the capital adequacy ratio (CAR) increased, reflecting a stronger capital structure. In terms of profitability, return on equity (ROE) showed an increase, the non-performing loan (NPL) ratio remained stable below 2%, and the operating expense to operating income (BOPO) ratio decreased. These findings reflect good efficiency and financial performance during the period analyzed. This research shows that BCA is able to maintain financial stability and improve performance even in the midst of changing economic dynamics.